Prospective Validation of the Preschool Confusion Assessment Method for the ICU to Screen for Delirium in Infants Less Than 6 Months Old. Issue 10 (October 2021) - Canter, Marguerite O.; Tanguturi, Yasas C.; Ellen Wilson, Jo; Williams, Stacey R.; Exum, Sylvia A.; Umrania, Hiren M.; Betters, Kristina A.; Raman, Rameela; Ely, E. Wesley; Pandharipande, Pratik P.; Fuchs, D. Catherine; Smith, Heidi A. B.
Abstract : OBJECTIVES: ICU delirium is a predictor of greater morbidity and higher mortality in the pediatric population. The diagnostic obstacles and validity of delirium monitoring among neonates and young infants have yet to be fully delineated. We sought to validate the Preschool Confusion Assessment Method for the ICU in neonates and young infants and determine delirium prevalence in this young population. DESIGN: Prospective cohort study to validate the Preschool Confusion Assessment Method for the ICU for the assessment of ICU delirium in neonates and young infants compared with the reference standard, Child and Adolescent Psychiatry. SETTING: Tertiary medical center PICU, including medical, surgical, and cardiac patients. PARTICIPANTS: Infants less than 6 months old admitted to the PICU regardless of admission diagnosis. MEASUREMENTS AND MAIN RESULTS: We enrolled 49 patients with a median age of 1.8 months (interquartile range, 0.7–4.1 mo), 82% requiring mechanical ventilation. Enrolled patients were assessed for delirium in blinded-fashion by the research team using the Preschool Confusion Assessment Method for the ICU and independently assessed by the psychiatry reference rater using Diagnostic and Statistical Manual of Mental Disorders-5 criteria. A total of 189 paired assessments were completed, and the Preschool Confusion Assessment Method for the ICU performed with a sensitivity of 95% (95% CI, 89–100%), specificity of 81% (68–90%), "negative and positive predictive values" of 97% (94–100%) and 69% (55–79%), respectively, compared with the reference rater. Delirium prevalence was 47%, with higher rates of 61% observed among neonates (< 1 mo old) and 39% among infants 1–6 months old. CONCLUSIONS: The Preschool Confusion Assessment Method for the ICU is a valid screening tool for delirium monitoring in infants less than 6 months old. Delirium screening was feasible in this population despite evolving neurocognition and arousal architecture. ICU delirium was prevalent among infants. The consequence of acute brain dysfunction during crucial neurocognitive development remains unclear. Future studies are necessary to determine the long-term impact of ICU delirium and strategies to reduce associated harm in critically ill infants.